COMPARISON OF EFFICIENCY OF LOCAL THRESHOLDING ALGORITHM AND THE PROPOSED ALGORITHM FOR SEGMENTATION OF SPACE OBJECTS’ (SO) IMAGES AGAINST THE STARRY SKY BACKGROUND - Strygin, N. Z.; Sukhov, P. P.; Karpenko, G. F. (Одеські астрономічні публікації, 2009)
In the article are presented comparative results of the space objects separation algorithms test on the television images of the sidereal sky regions – both the local thresholding method with the scanning apertures of various sizes and the new algorithm developed at the OAO. Advantages of the OAO algorithm are shown.